Prosthetic rehabiliation of anotia: a sense of emotional relief - Kuthiala, Abhinav; Patel, Disha; Basu, Debaditya; B., Nidhin S. (International Journal of Advances in Medicine, 2019)
Microtia is the abnormal development of the external ear that results in a malformed auricle. The deformity that results can range from mild distortion of the anatomic landmarks to the complete absence of the ear which is anotia. An otolaryngologist can expect to be called on to evaluate this defect several times in the average career. Although not every otolaryngologist will perform the complex surgical reconstruction of these malformations, one should be familiar with the aetiology, anatomy, medical management, and nonsurgical options available. The loss of an ear has a considerable psychological impact on an individual. Maxillofacial prostheses replace the lost body parts by using the silicone materials in order to alleviate these problems, prosthesis may be fabricated. This clinical report portrays a method to fabricate silicone auricular prosthesis for a patient who had congenital anotia. These prostheses support the patients physically as well as psychologically enhancing their confidence and social acceptance.